2014
DOI: 10.1021/ic402723c
|View full text |Cite
|
Sign up to set email alerts
|

Selective Fluorescence Sensing of Copper(II) and Water via Competing Imine Hydrolysis and Alcohol Oxidation Pathways Sensitive to Water Content in Aqueous Acetonitrile Mixtures

Abstract: Addition of hydrazines to a 1,8-disubstituted anthraquinone macrocycle containing a polyether ring produces site-selective imination, where hydrazone formation produces the more sterically hindered adduct. Reduction of the remaining carbonyl group to a secondary alcohol followed by addition of copper(II) ion causes intense yellow fluorescence to occur, which is selective for this metal cation and allows this system to be used as a fluorescence sensor. In the presence of water, a green-fluorescent intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The researchers have demonstrated that Zn 2+ ion possesses strong affinity toward Pi, which could be used as secondary probes for Pi, so that it is reasonable using Pi snatching Zn 2+ ion from the formed complex and releasing the free probe, leading a recovery optical signal of free probe. The major deficiencies of Zn 2+ probes reported are the interference from other transition metal ions, especially Cd 2+ , due to in the same group of the Periodic table and similar properties . Although a small amount of fluorescent probe is enhanced, its fluorescence excitation and emission wavelengths (usually less than 350 and 500 nm) are shorter, which suffers from background interference and low collection efficiency in deep‐tissue imaging .…”
Section: Introductionmentioning
confidence: 95%
“…The researchers have demonstrated that Zn 2+ ion possesses strong affinity toward Pi, which could be used as secondary probes for Pi, so that it is reasonable using Pi snatching Zn 2+ ion from the formed complex and releasing the free probe, leading a recovery optical signal of free probe. The major deficiencies of Zn 2+ probes reported are the interference from other transition metal ions, especially Cd 2+ , due to in the same group of the Periodic table and similar properties . Although a small amount of fluorescent probe is enhanced, its fluorescence excitation and emission wavelengths (usually less than 350 and 500 nm) are shorter, which suffers from background interference and low collection efficiency in deep‐tissue imaging .…”
Section: Introductionmentioning
confidence: 95%
“…Consequently, the proposed mechanism is depicted as follows (Scheme 2): Cu 2+ firstly coordinates with two adjacent nitrogen of diaminomaleonitrile moiety followed by the cleavage of the C=N bond to yield aldehyde-BODIPY 3, which was further oxidized into 4 by Cu 2+ in acetonitrile. [68][69][70] Job's plot experiment was carried out to determine the binding stoichiometry of the reaction. As shown in Fig.…”
Section: Mechanism Studymentioning
confidence: 99%
“…From the fluorescence titration experiment, the association constant of the receptor 64 toward the Pb 2+ , Zn 2+ and Cu 2+ were calculated to be 8800, 510 and 55000 M −1 , respectively revealed the highest tendency of the receptor 64 toward the copper ion in comparison to the Pb 2+ and Zn 2+ due to highest value of association constant. Mariappan et al 150 reported the selective fluorescence sensing of copper(II) and water via competing imine hydrolysis and alcohol oxidation pathways sensitive to water content in aqueous acetonitrile mixtures (Fig. 55.…”
Section: Bodipy Based Cu 2+ Sensormentioning
confidence: 99%